2006
DOI: 10.1002/yea.1347
|View full text |Cite
|
Sign up to set email alerts
|

Basic methods for fission yeast

Abstract: The fission yeast Schizosaccharomyces pombe is a popular model system, and has been particularly influential in studies of the cell cycle and chromosome dynamics. Despite its differences from Saccharomyces cerevisiae, the tools and methods for fission yeast are conceptually similar to those used in budding yeast. Here, we present basic methods sufficient for a beginner in this system to carry out most required manipulations for genetic analysis or molecular biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
500
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(506 citation statements)
references
References 25 publications
(22 reference statements)
5
500
0
1
Order By: Relevance
“…The induced level is about 806 greater than the repressed level. pREP41 has a 66 lower induced level and a 156 lower repressed level than the wild-type promoter (Basi et al, 1993;Maundrell, 1993;Forsburg & Rhind, 2006). As expected, HRP-PNA staining showed that galactosylation of the cell surface of the uge1D strain was restored in an expression-dependent manner (Fig.…”
supporting
confidence: 70%
“…The induced level is about 806 greater than the repressed level. pREP41 has a 66 lower induced level and a 156 lower repressed level than the wild-type promoter (Basi et al, 1993;Maundrell, 1993;Forsburg & Rhind, 2006). As expected, HRP-PNA staining showed that galactosylation of the cell surface of the uge1D strain was restored in an expression-dependent manner (Fig.…”
supporting
confidence: 70%
“…YN001 (msy1ura4 + in FY15952), YN002 (msy2kanMX6 in FY15952), YN003 (msy1ura4 + msy2kanMX6 in FY15952) and YN004 (msy1 + -4HA in FY15952) were created in this study. Cells were cultured at 30 °C in rich medium (YES) or synthetic medium (EMM2) 37 . E. coli strain PB113 (∆mscs ∆msck) was used for the electrophysiological experiment 38 .…”
Section: Methodsmentioning
confidence: 99%
“…General methods to handle fission yeast cells were as described (Forsburg and Rhind, 2006). Highefficiency transformation of Sz.…”
Section: Genetic Methods and Transformation Of Sz Pombementioning
confidence: 99%
“…Complete medium (YE; 0.5% yeast extract, 2% glucose, 5 µg/ml adenine), minimal medium (SD), and minimal medium (MM) were used for the culture of Sz. pombe cells (reviewed by Forsburg and Rhind, 2006). Thiamine and leucine were added to the media at a final concentration of 15 µM and 50 µg/ml, respectively, when needed.…”
Section: Sz Pombe Strains and Mediamentioning
confidence: 99%